(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Cattle was introduced in Papua a long time ago. However, it was unpredictable to adapt to raise cattle. An explorative field study was performed in fifteen villages using participatory research to better understand the dynamics of cattle performances. Cattle farming system has been categorized in three types, i.e. small- and medium-sized systems. They used ANOVA and Kruskal-Wallis to analyze data. The finding of this research was that the three sizes of cattle farming in many components of good farming practices were similar (p>0.05). No large gap was found along the lines of farmers, cattle, and economic performance. West New Guinea’s Tropical Livestock Unit was low and has the potential to increase due to agribusiness potential. Better government services and other related stakeholders should narrow the lack of good agricultural practices.